Prevalence, risk factors and attitude of parents towards childhood obesity among school children in Bangalore city - Dasappa, Hemavathi; Fathima, Farah Naaz; Ganesh, Krithika; Prasad, Shankar (International Journal Of Community Medicine And Public Health, 2018)
Background: Aim of the study was to determine the prevalence, risk factor attitude of parents towards obesity and overweight among the school children between the age group of 6-13 years. Methods: A structured questionnaire was filled by the parents and weight and height was measured by school nurse in a private school in Bangalore city. Results: Prevalence of overweight was 13.20% and obesity was 17.13%. Birth weight and sport was strongly associated with the prevalence. Sports protect the child from the overweight and obesity. Parent’s perception about their child’s BMI status was good. Parent’s attitude of having meal with their child and their estimation of child’s physical activity was protective and the attitude of controlling diet of the child was a risk factor for overweight and obesity. Though the parents were able to estimate their child as overweight and obese they were not willing for further advice. Conclusions: Prevalence of overweight and obesity is increasing. Higher birth weights, parental attitude of controlling child’s diet are the potential risk factors. Involvement in sports, parental attitude of having food with child and awareness about their physical activity are protective.